STUDY OF DUPLICATED OPTIC CANALS IN EASTERN INDIAN HUMAN SKULLS - Nayak, Gyanaranjan; Mohanty, Biswa Bhusan; Das, Saurjya Ranjan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The duplication of optic canals is a rare anomaly found in both sexes, all ages, and various races. The present study was carried out to find the incidence of duplication of optic canal and to study its clinical and developmental significance. Methods: The study included 100 dry human skulls of both the sexes and various age groups. These skulls were studied grossly and morphologically to find out duplication of the optic canals. Results: Additional optic canals were found in 3 skulls (3% cases). Out of them, 2 cases (2%) presented bilateral duplication, whereas in only one case (1%), it was unilateral. Conclusion: Knowledge of additional optic canals is of paramount importance in performing surgical exploration of the optic canal during removal of tumors or decompression of optic canals or surgically accessing the cavernous sinus or sella turcica. Keywords: Optic canal, Duplication, Anatomy, Skull.